Management Guides to Mergers and Acquisitions (Book). - Sterling, Robert R.; Hendrickson, Harvey S. (The Accounting Review, 1970)
Reviews the book "Management Guides to Mergers and Acquisitions," by John L. Harvey and Albert Newgarden.